High fat feeding impairs endothelin-1 mediated vasoconstriction through increased iNOS-derived nitric oxide - Sweazea, Karen L. (2011)
Rats fed a high fat diet develop increased adiposity and oxidative stress leading to impaired vasodilation. The purpose of the present study was to examine the effects of high fat-induced increases in adiposity and oxidative stress on vasoconstrictor reactivity of isolated mesenteric arteries. We hypothesized that rats with more adiposity would develop oxidative stress-potentiated increases in iNOS-derived nitric oxide leading to diminished vasoconstriction. Male Sprague-Dawley rats were fed either a control (Chow) or high fat diet for 6 weeks. The roles of oxidative stress and iNOS in the impaired vasoconstrictor responses to endothelin-1 were characterized in small mesenteric arteries. Rats fed the HFD developed significantly more adiposity compared to Chow rats. Plasma levels of nitric oxide and the inflammatory factor tumor necrosis factor α were significantly higher in high fat fed rats compared to Chow rats (nitric oxide: 95.36 ± 19.3 vs. 38.96 ± 6.7 μM; tumor necrosis factor α: 598 ± 111.4 vs. 292 ± 71.8 pg/mL, respectively). Despite exhibiting elevated systolic blood pressure compared to Chow rats (153.5 ± 2.4 vs. 137.5 ± 2.7 mmHg), endothelin-1 mediated vasoconstriction was impaired in isolated mesenteric arteries from high fat fed rats but was normalized by individual or combined inhibition of nitric oxide synthase, iNOS, or oxidative stress. Therefore, oxidative stress and iNOS are involved in the attenuation of endothelin-1 mediated vasoconstriction observed in isolated mesenteric arteries from high fat fed rats.